DESENVOLVIMENTO DE MODELO PARA PREDIÇÃO DA FRAÇÃO DIGESTÍVEL DA FIBRA EM DETERGENTE NEUTRO PARA BOVINOS EM CONDIÇÕES TROPICAIS - SILVA, Tadeu Eder da; DETMANN, Edenio; PALMA, Malber Nathan Nobre; AMORIM, Larissa Camacho Frota; VALADARES FILHO, Sebastião de Campos (Brazilian Journal of Biometrics, 2018)
The aim of this work was to propose a model to predict the digestible fraction of neutral detergent fiber (NDF) of forages and concentrates offered to cattle managed under tropical conditions as an alternative to the current model adopted by the BR-CORTE System. Two studies were carried out. The first one aimed to build models that could allow fractionating the NDF from forages and concentrates with regard its potential of ruminal degradation by using chemical characteristics. It were used 371 samples of forages and 65 samples of concentrates. The models built for both types of samples were based on the prediction of potentially digestible NDF (pdNDF). The second study aimed to build a model to predict the digestibility of pdNDF. The model was built from information of 60 animals receiving exclusively forage-based diets. The mathematical was based on integrating the ruminal degradation and ruminal passage rates of pdNDF and on average utilization of fiber in the large intestine. The comparative evaluation between the new model and the model adopted by the BR-CORTE System was performed using information of forages and concentrates from the CQBAL 3.0 database. The estimates of the digestible NDF obtained from the new model were more accurate and precise than the estimates obtained from current BR-CORTE model.